LISTENING CLASS AND MORAL EDUCATION - Prancisca, Stella; Rizqi, M. Ainur (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
Since some students including in my class become more self-oriented and less aware on group, there is a need to integrate online teaching material which contains values in society into English language course. We believe that English language teaching, in some extents, could facilitate this necessity. A good choice of material, for example, is not only beneficial to promote students language skill, but also could inspire students to become a better individual. This paper aims to examine whether online materials could promote students English language skill, especially in listening comprehension. In addition, it is keen to better understand how these resources could influence and develop their moral values. The paper is designed as a classroom action research. To collect data, we employ two tests (pre-and post-test), questionnaires, and interview. Since this paper is still a research design, it should be noted that there is no finding and discussion yet here.